Materials on the history of al-Farabi’s manuscripts at al-Biruni Institute of Oriental Studies, Academy of Sciences of Uzbekistan: history and prospects of research - Imangaliyev Almas,; Dukenbayeva Zadash,; Muhammad Hilmi Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Today, al-Biruni Institute of Oriental Studies, Academy of Sciences of Uzbekistan has more than 26000 volumes of manuscript collection, collected since the 10th century AD until now. Among the important manuscript collections found in this institute are manuscripts related to al-Biruni. This article aims to present and show the above catalogs of al-Farabi’s manuscripts in different directions of science. This catalog consisted of 14 volumes of Sobranie Vostochnyh rukopisi Akademii nauk Respubliki Uzbekistan (English translation: Collection of Oriental Manuscripts of the Academy of Sciences of the Republic of Uzbekistan). This article discusses the list and description of the manuscript of al-Farabi, which is in the above catalog. This paper found that al-Farabi’s manuscripts at this institute are a significant example of the interaction, unity, and integration between religion and science.